Direction of arrival estimation for passive bistatic radar - Yin, Tiantian (2016)
Direction of arrival (DOA) estimation algorithms provide estimations of the directions in which signals are impinging on the antenna array in radar systems. This report presents a comprehensive study on common DOA estimation methods used for uniform linear array (ULA). Three categories of twelve DOA estimation methods have been studied and implemented in MATLAB. These implementations provide an independent toolbox for convenient use in passive bistatic radar signal processing. The performances of the implemented DOA estimation algorithms have been simulated and compared in terms of different input signal to noise ratio, number of array elements and number of snapshots. In addition, the resolutions and accuracies of the implemented DOA estimation methods are compared based on two metrics including minimum angular separation and root-mean-square errors. For spectral-based methods, MUSIC algorithm has been found to have the highest resolution. For monopulse and parametric methods, root-MUSIC algorithm has been found to have the highest accuracy. In addition to the DOA estimation methods, two kinds of DOA schemes for passive bistatic radar systems have also been studied and implemented. In the absence of interference, the DOA scheme with conventional DOA estimation technique applying in the range-Doppler domain after matched filter has better performance than the DOA scheme applying conventional beamforming in the time domain before matched filter.